Student’s progress management, inventory and revenue calculation system: A brief analysis on BRAC Kumon Limited’s report AB - Islam, Muhammad Nazmul (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.